1982
DOI: 10.2134/jeq1982.00472425001100010029x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Mobilization Following Winter Fires in an Irregularly Flooded Marsh

Abstract: The effects of prescribed winter burning on nutrient pools in an irregularly flooded marsh in St. Louis Bay, Miss., were investigated. Nutrient levels were determined in field‐collected pre‐fire vegetation, post‐fire regrowth, pre‐fire and post‐fire sediments, combustion residues, and reference materials from unburned adjacent sites. Post‐fire soil chemistry was characterized by transitory elevation of sediment‐water pH, P extractable in 0.10N HCl + 0.03N NH4F, and exchange + solution phase K, Ca, and Mg in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Increases in PO 4 and soil cations were attributed to ash deposition (Schmalzer and Hinkle 1992). In contrast, the results of winter burning of Juncus and Spartina marsh communities on the Mississippi Gulf Coast suggested that increases in extractable P were the result of mild heating of organic sediments, and the retention of ash-derived nutrients may be a function of meteorological factors, tidal regimes, and topography (Faulkner and de la Cruz 1982).…”
Section: Wetland Fire Effects and Soil Nutrient Responsesmentioning
confidence: 98%
“…Increases in PO 4 and soil cations were attributed to ash deposition (Schmalzer and Hinkle 1992). In contrast, the results of winter burning of Juncus and Spartina marsh communities on the Mississippi Gulf Coast suggested that increases in extractable P were the result of mild heating of organic sediments, and the retention of ash-derived nutrients may be a function of meteorological factors, tidal regimes, and topography (Faulkner and de la Cruz 1982).…”
Section: Wetland Fire Effects and Soil Nutrient Responsesmentioning
confidence: 98%
“…Such dif-ferences have been observed in previous studies. Faulkner and de la Cruz (1982) found that K increased immediately postburn in the Juncus marsh and remained high 1 mo later; a small K increase occurred 26 da postburn in Spartina that was greater 68 da postburn. Calcium increases were greater immediately postburn in Juncus than 1 mo later; Spartina marshes had high Ca values I and 2 mo postfire.…”
Section: Discussionmentioning
confidence: 85%
“…PO4-P increased immediately after fire in the Juncus and Spartina marshes studied by Faulkner and de la Cruz (1982) and remained elevated. Wilbur and Christensen (1983) found increased PO4-P through the first growing season postfire.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations